Therapy terhadap Penyembuhan pada Ulkus Diabetikum: Literature Riview - Ismiati Ismiati; Wirsma Arif Harahap; Elvi Oktarina (Universitas Batanghari Jambi, 2023)
Diabetic ulcer is a disease that greatly affects the patient's quality of life, where the end of the course of the disease is that the patient must undergo an amputation. In Indonesia, diabetes shows an increasing incidence. Diabetic wounds that don't heal are a risk factor for infection and a major cause of amputations and death. One way of treatment is by treating wounds using the Negative Pressure Wound Therapy technique for healing diabetic ulcers. The research method used is a systematic review by identifying journal articles published online consisting of English in 2018-2021. Articles were retrieved using search engine tools PubMed, ScienceDirect, and JSTOR. There are 5 journals based on inclusion criteria. The results showed that there was an effect of wound care using the Negative Pressure Wound Therapy technique on the healing of diabetic ulcers.